MODAL SOSIAL DAN PEMBANGUNAN KETAHANAN PANGAN BERKELANJUTAN - Suandi, Suandi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
The purpose of the study are (1) Identify the various characteristics of household food security in rural areas, (2) Identify the social capital that developed in rural areas, (3) Identify the various characteristics of sustainable food security in rural areas and (4) Analysis of social capital on development of sustainable food security in various community groups. The study design was cross sectional. The study was conducted in Kerinci regency, by the time the research for 8 (eight) months of the calendar. Research variables: (1) family food security (availability, accessibility, and utilization of food and nutrition, (2) social capital (local associations and public characters), and (3) Sustainable food security (ecology, economic status, and sosio-demographic), with the number of respondents 165 households. The data were analyzed using models of Structural Equation Modelling (SEM) by LISREL program. The results showed: (1) the level of household food security in Kerinci regency good views of availability, accessibility and household utilization of nutrients obtained quite enough and stable. Respondents in the study area has a fairly high level of stability of food consumption (energy and protein consumption), (2) social capital in the study area owned by households is high and good views of the local association level as well as from the aspect of interaction and community character, (3) sustainable food security is enough high, (4) social capital (local associations and public characters) either directly or indirectly have a positive highly significant to the development of food security and sustainable food security. That is, the higher and varied levels of social capital owned by the family, the more stable the level of food security so that the turn can improve the sustainable food security of the family.